Respuesta :

x=4

Simplifying

2x + 6 = 4x + -2    

Reorder the terms:

6 + 2x = 4x + -2

Reorder the terms:

6 + 2x = -2 + 4x

Solving

6 + 2x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.

6 + 2x + -4x = -2 + 4x + -4x

Combine like terms: 2x + -4x = -2x

6 + -2x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0

6 + -2x = -2 + 0

6 + -2x = -2

Add '-6' to each side of the equation.

6 + -6 + -2x = -2 + -6

Combine like terms: 6 + -6 = 0

0 + -2x = -2 + -6

-2x = -2 + -6

Combine like terms: -2 + -6 = -8

-2x = -8

Divide each side by '-2'.

x = 4

Simplifying

x = 4